Rugby league, and factors which may have an associative impact on the frequency, intensity and type of injury: A review of current literature - Thompson, K. (Journal of Australian Strength and Conditioning, 2013)
The purpose of this review is to identify factors which may lead to injuries sustained in rugby league, with the aim being to assist strength and conditioning coaches to devise programs which may help to prevent and minimise injuries and their recurrence, and shorten the recovery time. The literature reviewed deals with training loads in pre-season and match play, physical collision in skills training and match play, and training and match intensity. Also reviewed is literature dealing with injury related to playing position and the site, nature and cause, a tackling time and motion study, and the physiological demands placed on players. A National Rugby League (NRL) season report collates the available data and highlights the difficulty of reporting, recording and comparing data. The findings suggest the cause of injury is multi-factorial, and that there is a significant relationship between injury and training load, which may lead to fatigue and the risk of over-training. The majority of injuries result from collision, and appear to be related to playing position, with the most common site being the lower body. Muscular injury is the most common type overall. The incidence of injury is lower in elite athletes, and most training injuries occur in the first half of the pre-season, while most match play injuries occur in the second half of the in-season. Strategies which may lower the incidence of injury include creating individual athlete profiles to determine optimal training loads, position specific and individualised training, phase related training loads, markers such as pre and post training assessments to determine intensity rating and avoid performance decrement and over training, and a non-invasive rating system, including perceptual measures, to establish the individual athlete`s stress tolerance level to training load, fatigue and recovery.